Collective evolution of surface microcrack for compacted graphite iron under thermal fatigue with variable amplitude. (January 2019) - Pan, Sining; Yu, Gang; He, Xiuli; Li, Shaoxia; Zhang, Yue; Li, Qingyu
Highlights: The collective evolution of surface microcrack is studied systematically. As the test goes on, the fractal dimension increases following the Hill's function. Tmax in the heating stage mainly affects the number of main microcrack. NHCF in the high-cycle stage mainly affects the number of secondary microcrack. The results help to evaluate damage degree and predict lifetime of material. Abstract: With the growing demand of good performance and high reliability of the heated components, the cracking failure caused by the complex thermal loading of variable amplitude has become a crucial problem. The collective evolution of surface microcrack for compacted graphite iron under thermal fatigue with variable amplitude is studied in this paper, which is induced by pulsed laser. The thermal microcrack is analyzed with statistic method and fractal method systematically. The result shows that, the secondary microcrack is the primary crack pattern, and the number of main microcrack is the least. As the test goes on, the fractal dimension increases following the Hill's function. Furthermore, the effect of maximum temperature Tmax and superimposed number NHCF on the crack evolution is investigated. Tmax in the heating stage mainly affects the number of main microcrack. With the increase of plastic strain amplitude, the fractal dimension increases exponentially, and gradually tends to be the critical fractal dimension D0 of 1.395. The superimposed number NHCF in the high-cycle stage mainly affects the number of secondary microcrack. The fractal dimension increases exponentially with the increase of NHCF, and tends to be the critical fractal dimension D0 of 1.404. The analysis of the collective behavior of surface microcrack is helpful for evaluating the damage degree and predicting the lifetime, which can be applied to other materials working under thermal loading of variable amplitude.